The Utilization of Digital Communication Media Genre Radio in Successful BKKBN Programs - yasha langitta setiawan; Puryanto Puryanto; Januardi Nasir (MediaTor (Jurnal Komunikasi), 2021)
The development of communication technologies has changed people's lives who are now more likely to use Internet-based or digital communication media. BKKBN West Sumatra is a government agency which innovates by using digital media called "GenRe Radio." This study aims to examine the use of the digital radio communication media genre in population programs, family planning, and family development and analyse the communication process performed by genre radio in the content of broadcasting programs. The research method used is a qualitative method based on a case study. The sample collection technique in this study was based on purposive sampling techniques. Informants in this study amounted to six people. This research shows that BKKBN uses digital radio communication media to transmit information about population, family planning, and family development in western Sumatra. The utilization of the digital radio communication media genre can increase the use of birth control and the suitable age to marry. Information and inducements to attract listeners are conveyed through the official Instagram post @genreradio107.9fm. The public can also participate in interactive talk show broadcast programs.